Auf der Suche nach Zukunft - Rathfelder, André (2023)
In the fifty years since the publication of ‘The Limits to Growth’, an inconceivably endless pool of ideas on how to respond to our ecological crisis has emerged. This book provides guidance by offering a comprehensive and in-depth look at the landscape of ecologically motivated political ideas, focusing on the discourse in German-speaking countries. Major currents of green political thought are presented and linked to their thought leaders. The book discusses the crucial dividing lines between these competing positions and analyses their development over time. It thus provides a significant contribution to exploring the field of green political thought and thereby strengthens the theoretical foundation of today’s discourses on ecological transformation.